2007
DOI: 10.1007/s11019-007-9112-0
|View full text |Cite
|
Sign up to set email alerts
|

Substitute decision making in medicine: comparative analysis of the ethico-legal discourse in England and Germany

Abstract: Health care decision making for patients without decisional capacity is ethically and legally challenging. Advance directives (living wills) have proved to be of limited usefulness in clinical practice. Therefore, academic attention should focus more on substitute decision making by the next of kin. In this article, we comparatively analyse the legal approaches to substitute medical decision making in England and Germany. Based on the current ethico-legal discourse in both countries, three aspects of substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
0
20
0
2
Order By: Relevance
“…Furthermore, a study [19] has shown that a large majority of French nurses and doctors were in favour of families being involved in decision making. Table 1 shows the legal measures of eight European countries regarding patients' rights, the validity of advance directives and the rights granted to a surrogate, designated or not [4, 20,21,22 ]. The viewpoints of these countries are consistent with the patient autonomy model.…”
Section: Surrogatesmentioning
confidence: 89%
“…Furthermore, a study [19] has shown that a large majority of French nurses and doctors were in favour of families being involved in decision making. Table 1 shows the legal measures of eight European countries regarding patients' rights, the validity of advance directives and the rights granted to a surrogate, designated or not [4, 20,21,22 ]. The viewpoints of these countries are consistent with the patient autonomy model.…”
Section: Surrogatesmentioning
confidence: 89%
“…Little is known in Europe about EOL decisions and ADs, particularly in patients with severe advanced disease 18 19. Switzerland is a multicultural and multilingual federal country and has the particularity of being divided into four linguistic and cultural regions.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, the new legal regulations in Germany harmonise well with the laws that other European countries have introduced recently 4 17. All of them affirm that an advance directive is in general a legally binding documentation of the patient's will.…”
Section: German Law In the European Contextmentioning
confidence: 55%
“…Although Germany is notorious for having meticulous legal regulations, this law is rather sketchy: it eschews many controversial issues like, for example, the decision-making capacity, the revocation of directives, the treatment of minors or advance care counselling. Compared with the German law, an example of a comprehensive and detailed statute is the English Mental Capacity Act 2005 17 18. In the international context the German law is quite liberal in that it does not stipulate many requirements for advance directives to be legally binding.…”
Section: German Law In the European Contextmentioning
confidence: 99%